2013
DOI: 10.1111/tmi.12165
|View full text |Cite
|
Sign up to set email alerts
|

HIV and Schistosoma haematobium prevalences correlate in sub‐Saharan Africa

Abstract: Abstractobjective Epidemiological studies have observed that genital schistosomiasis increases the risk of HIV infection in Africa. We analysed the correlation between Schistosoma haematobium prevalence and HIV prevalence across sub-Saharan African countries.design Regression analysis of prevalence of HIV and S. haematobium across sub-Saharan African countries. methods Using compiled country-level S. haematobium prevalence, HIV prevalence and other demographic and economic data from published sources, we appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 32 publications
1
26
1
Order By: Relevance
“…Despite the fact that schistosomiasis is a known risk factor for developing CKD [26] or acquiring HIV [27], we did not find a significant association in either case.…”
Section: Discussioncontrasting
confidence: 86%
“…Despite the fact that schistosomiasis is a known risk factor for developing CKD [26] or acquiring HIV [27], we did not find a significant association in either case.…”
Section: Discussioncontrasting
confidence: 86%
“…As if this information were not bad enough, several large epidemiological studies show that FGS is responsible for up to a three-to four-fold increase in horizontal transmission of HIV/ AIDS [2,7,8], whereas a regression analysis of prevalence of S. haematobium infection and HIV in sub-Saharan African countries found that each S. haematobium infection per 100 individuals resulted in a 3% relative increase in HIV prevalence [9].…”
mentioning
confidence: 99%
“…Patients may be subject to coinfections that alter symptoms, immune responses, and therapies (2-5). These are just 2 examples in which multiplexed platforms would provide timely, cost-effective diagnosis.…”
Section: Discussionmentioning
confidence: 99%